2015
DOI: 10.17352/2394-8418.000014
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Outcomes for Children in Hawaii: Not Much to Smile About

Abstract: Oral health has become a major topic of discussion in the State of Hawaii based on the unreasonably high rates of dental caries in children, which are almost twice the average rates for children living in the mainland. Lack of water fluoridation, absence of a state dental school and recent efforts to start rebuild the previously dismantled oral health branch at the Department of Health may be contributing to these poor oral health outcomes. However, there are many more known caries risk factors which may be so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Several factors play a role in determining the oral health outcomes of children and families 5 . In the State of Hawaii, families experience several challenges to accessing oral health services.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors play a role in determining the oral health outcomes of children and families 5 . In the State of Hawaii, families experience several challenges to accessing oral health services.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors play a role in determining the oral health outcomes of children and families. 5 In the State of Hawaii, families experience several challenges to accessing oral health services. Children living in rural and underserved areas of the islands are less likely to receive preventive dental visits, with parents noting that transportation, scheduling inconveniences, and inability to take time off from work are barriers to taking children to dental appointments.…”
mentioning
confidence: 99%
“…States that rely on fluoride sources other than water, such as Hawaii, where less than 9% of the population receives fluoridated water, experience some of the poorest oral health outcomes. Hawaiian children suffer from dental caries at almost twice the average rates of those reported for mainland children [35].…”
Section: Discussionmentioning
confidence: 88%
“…Dental caries, one of the most common chronic infections in childhood, is a disease that results in disruption of the integrity of dental hard tissues [16,17]. In studies conducted in Turkey, it is observed that the prevalence of caries in children aged 2-15 years ranges between 43.5% and 84.9% with an increasing trend [18,19].…”
Section: Discussionmentioning
confidence: 99%